PENGARUH MEDIA TANAM PADA PEMBIBITAN TANAMAN TELANG (Clitoria ternatea L.) - Sundari Sundari; Syahrani Syahrani; Feriska Ayu Firmadari (Jurnal Magrobis, 2021)
This study aimed to determine the effect of planting media on telang plant nurseries. This research started from April to June 2021, carried out in Bukit Biru Village, Tenggarong sub district, Kutai Kartanegara Regency. This study used a randomized block design (RCBD) which was repeated 5 times. Media treatment (T) consisted of five levels, namely: t0 (soil), t1 (soil and raw husk 1:1), t2 (soil and raw husk 1:2), t3 (soil and burnt husk 1:1), t4 (burnt soil and husk 1:2). Planting media treatment had no significantly effect on the average age of shoot emergence, plant height at the age of  21 DAP (days after planting), the number of leaves at the age of 14 and 28 DAP. Planting media treatment had a significantly effect on the average of plant height at 14 DAP (days after planting) and had a very significantly effect on the average of plant height at 28 DAP (days after planting). Better treatment on t3 treatment (soil and burnt husk 1:1), on shoot emergence, plant height, and number of leaves parameters.